Pengaruh solvabilitas, profitabilitas, ukuran perusahaan dan ukuran Kantor Akuntan Publik terhadap audit delay - Amelia Oktrivina; Widyaningsih Azizah (LPMP Imperium, 2022)
This study aims to determine the effect of solvency, profitability, firm size and public accounting firm size (KAP) on audit delay. By conducting an empirical study on the Main Board Energy Sector Company Industry Listed on the Indonesia Stock Exchange (IDX) in (2018-2020). In this study, there were 28 main board energy companies listed on the Indonesia Stock Exchange for the 2018-2020 period, with certain criteria so that the selected sample was 84 research samples. The sample of this study was selected using the purposive sampling method. This research was conducted using multiple linear analysis using the E-views 12 application. This study provides the results that (1) Solvency has an effect on audit delay. (2) Profitability has no effect on audit delay. (3) Firm size has no effect on audit delay.(4) The size of the Public Accounting Firm (KAP) has an effect on audit delay.